Reducing Oral Health Disparities: A Focus on Social and Cultural Determinants - Grembowski David; Nucci Michele; Lee Rosanna; Patrick Donald L; Jolles Carol; Milgrom Peter (BMC, 2006)
Abstract Oral health is essential to the general health and well-being of individuals and the population. Yet significant oral health disparities persist in the U.S. population because of a web of influences that include complex cultural and social processes that affect both oral health and access to effective dental health care. This paper introduces an organizing framework for addressing oral health disparities. We present and discuss how the multiple influences on oral health and oral health disparities operate using this framework. Interventions targeted at different causal pathways bring new directions and implications for research and policy in reducing oral health disparities.